Innovative methods of teaching histology, cytology and embryology at medical university in the hybrid format of the educational process - Aliyeva, O. H.; Pototska, O. I.; Tavrog, M. L.; Gromokovskа, T. S.; Makyeyeva, L. V.; Popazova, O. O.; Алієва, Олена Геннадіївна; Потоцька, Олена Іванівна; Таврог, Маріанна Львівна; Громоковська, Тетяна Сергіївна; Макєєва, Людмила Валеріївна; Попазова, Олена Олександрівна (My University, 2025)
The war in Ukraine has deeply affected all areas of society, including education. Following COVID-19 restrictions and the imposition of martial law, distance learning became the safest and most accessible option for students, regardless of their location, and has remained prominent.
Keywords: тези доповідей